Learn Multiply Pq Minus 2r Pq Minus 2r

from a handpicked tutor in LIVE 1-to-1 classes

from a handpicked tutor in LIVE 1-to-1 classes

# Multiply: (pq - 2r), (pq - 2r)

**Solution:**

Given, __multiply__ (pq - 2r), (pq - 2r)

⇒ (pq - 2r) × (pq - 2r) = (pq - 2r)²

Using (a - b)² = a² - 2ab + b²

= [(pq)² - 2(pq)(2r) + (2r)²]

= p²q² - 4pqr + 4r²

**✦ Try This: **Multiply: (2a - bc), (2a - bc)

Given, Multiply: (2a - bc), (2a - bc)

⇒(2a - bc) × (2a - bc)

= (2a)² - 2abc - 2abc + (bc)²

= 4a² - 4abc + b²c²

**☛ Also Check: **NCERT Solutions for Class 8 Maths Chapter 9

**NCERT Exemplar Class 8 Maths Chapter 7 Problem 83(xvii)**

## Multiply: (pq - 2r), (pq - 2r)

**Summary:**

Multiplying (pq - 2r), (pq - 2r) we get, p²q² - 4pqr + 4r²

**☛ Related Questions:**

Math worksheets and

visual curriculum

visual curriculum